2019
DOI: 10.11591/ijpeds.v10.i4.pp2182-2189
|View full text |Cite
|
Sign up to set email alerts
|

Genetic algorithm to improve power output of photovoltaic system under partial shaded condition

Abstract: The Partial Shaded Condition (PSC) is a process of non-optimal power capture in photovoltaic (PV) system; it will happen when one or all the PV solar cells get shaded by external factors. This phenomenon makes a sudden change in cell irradiance and lead to non-optimal power capture and reduces the generated power in PV systems. Cell under PSC generates one global peak (GP) and many local peaks (LPs), but the tracking of GP under (PSCs) effectively are still a big challenge to the researchers. In this paper, Fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…From the Tables 1-4, it is observed that the charging system with hybrid GWO-CSA performs better under different conditions, and it extracts a good amount of power from PV. Power extracted in watts using PSO, EL-PSO [32], [33] Power extracted in watts using GA, FL [38], [39] Power extracted in watts using hybrid GWO Reference voltage in Volts using PSO, EL-PSO [32], [33] Reference voltage in Volts using GA, FL [38], [39] Reference voltage in Volts using hybrid GWO It is shown that the voltage regulation is better in hybrid GWO-CSA and the efficiency is also better in the proposed algorithm. Figure 9 shows the state of charge of the battery in all the cases using the proposed algorithm.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…From the Tables 1-4, it is observed that the charging system with hybrid GWO-CSA performs better under different conditions, and it extracts a good amount of power from PV. Power extracted in watts using PSO, EL-PSO [32], [33] Power extracted in watts using GA, FL [38], [39] Power extracted in watts using hybrid GWO Reference voltage in Volts using PSO, EL-PSO [32], [33] Reference voltage in Volts using GA, FL [38], [39] Reference voltage in Volts using hybrid GWO It is shown that the voltage regulation is better in hybrid GWO-CSA and the efficiency is also better in the proposed algorithm. Figure 9 shows the state of charge of the battery in all the cases using the proposed algorithm.…”
Section: Resultsmentioning
confidence: 98%
“…Salvi et al [38], fuzzy logic is used to analyse the problem of partial shaded conditions in PV. And [39] discusses the genetic algorithm in comparison with the fuzzy logic for the partial shaded problem in PV.…”
Section: Introductionmentioning
confidence: 99%
“…In this method, the Levy Flight concept is employed to control the PSO velocity equation when the random number is less than 0.25. Thus, the velocity of particles is updated using (12) and (13). On the other hand, when the random number is greater than or equal to 0.25, the conventional velocity equation is utilized as in (7).…”
Section: Overview Of Mppt Methods Based On Vpso-lf Algorithmmentioning
confidence: 99%
“…Recently, many methods based on meta-heuristic techniques have been utilized to track the MPP with considering the problem of partial shading conditions such as Genetic Algorithm (GA) [13], Cuckoo Search (CS) [14], Artificial Bee Colony (ABC) [15], Ant Colony Optimization (ACO) [16], Firefly (FA) [17], Grey Wolf Optimization (GWO) [18], Bat Algorithm (BA) [19], Flower Pollination Algorithm (FPA) [20], Teaching-learning-based optimization (TLBO) [21] and Particle Swarm Optimization (PSO) [22][23][24]. These methods were distinguished by their accuracy and high speed in tracking for the maximum power point in all environment conditions.…”
Section: Introductionmentioning
confidence: 99%
“…In order to overcome this problem, many approaches have been suggested [18], including the use of heuristic methods inspired by nature [19][20][21][22][23][24], such as: particle swarm optimization (PSO), proposed by Kennedy [25,26], In order to improve the performance of the structure of the PSO algorithm, a contribution was proposed in [27,28]. On the other hand, the development of the SCSO and SCA algorithms [29][30][31] and their contribution either by the optimization of the physical systems [32], or in the optimization of the FLC controllers [33], gave satisfactory results.…”
Section: Introductionmentioning
confidence: 99%